RURAL DEVELOPMENT INTHE BRAZILIAN AMAZON: LEVELS AND DISTRIBUTION IN THE 2000-2010 DECADE - MÁRIO SÉRGIO PEDROZA LOBÃO; JEFFERSON ANDRONIO RAMUNDO STADUTO (Ambiente & Sociedade, 2020)
Abstract This paper analyzes the rural development of Brazilian Amazon municipalities in the decade 2000-2010 based on an analysis of the Rural Development Indexes (RDI) calculated for 449 municipalities. The index calculation takes into account demographic, social/welfare, environmental and economic dimensions. The results showed that only 47.88% of the municipalities had rural development levels superior to the regional average. The study identified a high degree of heterogeneity in the intraregional distribution of rural development whereby municipalities with high levels coexisted with others with very low levels. The distribution of rural development showed a clear pattern of a duality: the eastern and southern portions of the Brazilian Amazon in the states of Rondônia, Pará and Tocantins had the best levels of development and the western and northern portions in the states of Acre, Amapá, Amazonas and Roraima had the worst levels.